Hormonal and metabolic response in elite female gymnasts undergoing strenuous training and supplementation with SUPRO(R) Brand Isolated Soy Protein - Stroescu, V.; Dragan, J.; Simionescu, L.; Stroescu, O. V. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: This study evaluates the metabolic and hormonal response in elite female gymnasts undergoing strenuous training and supplementation with SUPRO(R) Brand Isolated Soy Protein. METHODS: Experimental design: 14 top female gymnasts (Romanian Olympic Team), took part in a study to examine their hormonal metabolic profile and to investigate any possible changes resulting from a 4-month program of strenuous training and daily supplementation with soy protein at a level of 1 g/kg body weight. Gymnasts wtare randomly assigned to one of two groups seven to the Supplemented Group (A) and seven to the Non-Supplemented Group (B). Both groups took part in the same program, wich consisted of strenuous training for 4-6 hours/day (except on Sunday, controlled food intake and supplements including vitamins and minerals. Group A received a supplement of Sports Beverage Protein Mix with SUPRO(R) Isolated Soy Protein (ISP) twice daily. Group B received a placebo identical in appearance and flavour. Selected parameters were measured before and after the 4-month training program (lean body mass, fat mass, serum hemoglobin, protein, fats, urea and creatinine, liver enzymes, serum total calcium and magnesium, immunoglobulins, urinary mucoproteins, serum T3 and T4, estradiol, progesterone, prolactin, testosterone and urinary 17-ketosteroids). RESULTS: Results demonstrated that the Supplemented Group (A) had an increase in lean body mass and serum levels of prolactin (p<0.01) and T4 and a decrease in serum alkaline phosphetases (p<0.01). The Non-Supplemented Group (B) had a decreased level of serum T4 and an increased level of urinary mucoproteins (p<0.05). CONCLUSIONS: Our preliminary conclusions might suggest lower metabolic-hormonal stress in elite female gymnasts undergoing strenuous training and who received daily supplementation with isolated soy protein.